Історія скла під мікроскопом: з яких ракурсів варто досліджувати гутництво - Курдина, Ю. М. (Lviv Polytechnic Publishing House, 2016)
Проаналізовано основні підходи, принципи та методи, використання яких дає змогу цілісно та всебічно досліджувати історію скла. На прикладі гутництва кінця XV – I половини XIX ст. продемонстровано необхідність використання системного, проблемно-хронологічного та, особливо, міждисциплінарного підходів для забезпечення максимум детального дослідження цього господарського заняття. The history of glass is multifaceted and full of mysteries. It is impossible, however, to study glass-making in all its complexity of manifestations by using only historical methods. By the example of Hutta production in the late XV – the 1st half of the XIX centuries the article shows the necessity to use a multidisciplinary approach in order to provide a maximum detailed research of the history of glass. Hutta production as a multi-faceted phenomenon cannot be in the purview of history only. In particular, the basic materials according to which the reconstruction of Hutta production can be made are the results of archeological studies. This particularly includes structures of glass-melting furnaces and glassware. Generally, two categories of research activities are typical of archeology: study of material objects (formation of sources) and interpretation. The interrelation between these categories goes from collecting materials to their commenting. The determination of age of finds is also important because the tendency to making certain glass was specific to correspondent time periods and regions. The issues of Hutta production is also closely related to another line of research – history of art. The fact is that the art styles affected not only architecture or sculpture but were also reflected in glassware decoration techniques. For example, a characteristic feature of Baroque glassware was a pedestal of the stem made in the form of a petal. The research methods in this case are based on the analysis of the works of art that is typical of the science dealing with plastic (spatial) arts. The ethnographic studies confirm that even before the early XX century there existed a belief that a bear brings happiness into the house, it is no surprise, therefore, that the glassware in the form of a bear was particularly popular. A “bottle-bear” was a necessary attribute of a village wedding in the XVIII century etc. The application of methods and approaches of different sciences allows studying the history of glass under the microscope with different lenses.
Keywords: гутництво; методи дослідження; міждисциплінарний підхід; археологія; скло; hutta production; research methods; interdisciplinary approach; archeology; glass; 94 (477/ 930.2)